2013
DOI: 10.1007/s10549-013-2538-6
|View full text |Cite
|
Sign up to set email alerts
|

Germline mutations in NF1 and BRCA1 in a family with neurofibromatosis type 1 and early-onset breast cancer

Abstract: Neurofibromatosis type 1 (NF1) is a common dominant autosomal disorder caused by mutations in the NF1 gene. The main manifestations of NF1 are café-au-lait spots, neurofibromas, intertriginous freckling, Lisch nodules, and malignancy, including peripheral nerve sheath tumors, central nervous system gliomas, and a variety of other tumors not so clearly defined. The association between NF1 and breast cancer or other gynecologic malignancies seems uncommon and has been scarcely referred in the literature. We desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…Furthermore, most cases were ductal invasive carcinoma and less commonly lobular carcinoma (Table 2) [57, 1131]. Interestingly, we found one well-documented case of MBC (carcinosarcoma) [11].…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, most cases were ductal invasive carcinoma and less commonly lobular carcinoma (Table 2) [57, 1131]. Interestingly, we found one well-documented case of MBC (carcinosarcoma) [11].…”
Section: Discussionmentioning
confidence: 93%
“…Neurofibromin, the protein encoded by the NF1 gene, functions as a negative regulator of the ras oncogene pathway. Ras is an essential component of the signal transduction pathway that regulates cell growth, proliferation, differentiation, and apoptosis, and the impairment of the hydrolytic reaction is associated with an increased risk of cancer . Yoon et al have reviewed all of the reports of breast cancer in NF1 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The mastectomy specimen showed a foci of neurofibroma with benign clusters of peripheral nerves admixed with fibroblasts, which showed diffuse positivity for S100. To the best of our knowledge, Campos et al were the only group to report a family with individuals with diagnosis of NF1 and breast cancer who were carriers of both BRCA1 and NF1 mutations [12]. They concluded that the concurrence of NF1 and breast cancer was probably due to the simultaneous existence of two cancerpredisposing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the concurrence of NF1 and breast cancer was probably due to the simultaneous existence of two cancerpredisposing conditions. Most of the cases of breast cancer in NF1 individuals are diagnosed at an advanced stage with a T score greater than 2 [12,13]. Therefore, the worse prognosis of breast cancer in NF1 may not be a characteristic of the disease itself, but may result from late-stage diagnosis due to the presence of skin neurofibromas, which hinder its identification, or due to the delay in seeking medical care by patients who think the breast mass is a neurofibroma [14,15].…”
Section: Discussionmentioning
confidence: 99%